Homocysteine levels in preterm infants: is there an association with intraventricular hemorrhage? a prospective cohort study - Sharma Shailja; Mackley Amy B; Leef Kathleen H; Sturtz Wendy J; Bottiglieri Teodoro; Paul David A (BMC, 2007)
Abstract Background The purpose of this study was to characterize total homocysteine (tHcy) levels at birth in preterm and term infants and identify associations with intraventricular hemorrhage (IVH) and other neonatal outcomes such as mortality, sepsis, necrotizing enterocolitis, bronchopulmonary dysplasia, and thrombocytopenia. Methods 123 infants < 32 weeks gestation admitted to our Level III nursery were enrolled. A group of 25 term infants were enrolled for comparison. Two blood spots collected on filter paper with admission blood drawing were analyzed by a high performance liquid chromatography (HPLC) method. Statistical analysis included ANOVA, Spearman's Rank Order Correlation and Mann-Whitney U test. Results The median tHcy was 2.75 μmol/L with an interquartile range of 1.34 - 4.96 μmol/L. There was no difference between preterm and term tHcy (median 2.76, IQR 1.25 - 4.8 μmol/L vs median 2.54, IQR 1.55 - 7.85 μmol/L, p = 0.07). There was no statistically significant difference in tHcy in 31 preterm infants with IVH compared to infants without IVH (median 1.96, IQR 1.09 - 4.35 μmol/L vs median 2.96, IQR 1.51 - 4.84 μmol/L, p = 0.43). There was also no statistically significant difference in tHcy in 7 infants with periventricular leukomalacia (PVL) compared to infants without PVL (median 1.55, IQR 0.25 - 3.45 μmol/L vs median 2.85, IQR 1.34 - 4.82 μmol/L, p = 0.07). Male infants had lower tHcy compared to female; prenatal steroids were associated with a higher tHcy. Conclusion In our population of preterm infants, there is no association between IVH and tHcy. Male gender, prenatal steroids and preeclampsia were associated with differences in tHcy levels.